Programa de monitoreo en tiempo real de los sismógrafos del OVSICORI - Vargas-Chaves, Alejandro José (Instituto Tecnológico de Costa Rica, 2015)
Costa Rica has the peculiarity of being a country in which seismic events are frequent. The main reason behind this, is that the country is located in the Ring of Fire. To watch, analyze and interpret all seismic and volcanic movements that occur in the country, the Volcanology and Seismology Observatory of Costa Rica (OVSICORI) was created. For this reason it’s OVSICORI’s job to spread knowledge obtained from the seismic data to prevent and mitigate the disasters generated from volcanic and seismic activity. At the present time, OVSICORI lacks the necessary tools to show to the population all the information of seismic movements. To provide this information they depend mainly on the telephone line, in which the information provided is limited. For this reason project iReal of Tecnológico de Costa Rica and OVSICORI are working together with the intention to develop several projects to visualize seismic data. Taking advantage of this link between universities and with the intention to solve this need, it’s intended to develop a monitoring system of the seismographs in real time. The intention of this system is to obtain data from the OVSICORI seismic stations and show this information in their web page to the population in an easy way to comprehend. This tool not only pretends to obtain and register the information of an earthquake, it also intends to elaborate a simulation of the evolution of intensity sensed in different zones of the country. This document details all the process done to elaborate this software, which covers mainly these aspects:  Investigation of different concepts and tools of seismology  Needed protocols to obtain data from the seismological stations  Algorithms needed to filter the signal and methodologies to store this information so it can be shown in the application  Web tools that allow representation of seismographs and intensity simulation  Interpolation algorithms to elaborate the simulation Keywords: GIS, accelerogram, seismogram, seismograph, intensity, Leaflet, openGL, MiniSEED, seedlink, digital filter, IDW.
Monitoring program in real time of OVSICORI’s seismographs
Proyecto de Graduación (Licenciatura en Ingeniería en Computadores). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Computadores, 2015.
Keywords: Sismología.; Movimientos Tectónicos.; Herramientas: webs, algoritmos, estaciones